ABOUT THE MECHANISM OF FINANCIAL INCENTIVE FOR THE DEVELOPERS OF IT SYSTEMS - Alexey S. Dobrynin (Statistika i Èkonomika, 2016)
Improving the performance of the developers of hardware and software systems and IT systems it is inextricably linked with quality incentives. People are motivated to work and are able to achieve good results, focusing on decent remuneration. Non-rational approaches to remuneration are able to generate social problems and greatly reduce the overall efficiency of the organizational systems. Motivation mobile teams of IT developers and individuals engaged in the operational management of the project implementation is of paramount importance. The article examines the mechanisms for stimulating the synthesis development of IT systems based on the principle of coordinated control that allows you to bring together the interests of the customers and performers. It is expected that customers and performers interested in creating all the necessary conditions (investment, social, technological) to obtain high-quality final product. The customer agrees with the developer on the approximate number of design iterations, each iteration of the composition, timing and budgets required to achieve the desired result. By means of evaluating the effectiveness of business results are metric tests, including functional and modular (unit tests), created in direct contact representatives of the customer and the developer. This mechanism should be used in mobile teams, in which the development is relatively short iterations with stepwise refinement of business requirements.